Plasma‐activated medium triggers immunomodulation and autophagic activity for periodontal regeneration - Shengfang Wang; Peiyu Wang; Rik Thompson; Kostya Ostrikov; Yin Xiao; Yinghong Zhou (Wiley, 2023)
Abstract Periodontitis is an infection‐induced inflammation, evidenced by an increase in inflammatory macrophage infiltration. Recent research has highlighted the role of plasma‐activated medium (PAM) as a regulator of the innate immune system, where macrophages are the main effector cells. This study therefore aims to investigate the immunomodulatory effects of PAM on macrophages and its potential applications for periodontitis management. PAM was generated using an argon jet and applied to culture macrophages. Proinflammatory macrophage markers were significantly reduced after PAM stimulation, and this was correlated with the activation of autophagy via the Akt signaling pathway. Further investigations on the proregenerative effects of PAM‐treated macrophages on periodontal ligament cells (PDLCs) revealed a significant increase in the expression of osteogeneis/cementogenesis‐associated markers as well as mineralization nodule formation. Our findings suggest that PAM is an excellent candidate for periodontal therapeutic applications.